ANALYSIS OF THE INFLUENCE OF CAMELS FACTORS ON PROFITABILITY AT PT. BANK MANDIRI (PERSERO) TBK - Mayang Palupi; Nisrul Irawati; Chairul Muluk (PT. Radja Intercontinental Publishing, 2023)
This research aims to determine the effect of the CAMELS ratio on the financial profitability of PT. Bank Mandiri (Persero) Tbk. This research uses CAMELS ratios, namely Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), Interest Expenses to Total Loans (IETTL), Net Interest Margin (NIM), Operational Costs to Operating Income (BOPO), Loan to Deposit Ratio ( LDR) and Net Open Position (PDN) on financial profitability as measured using Return On Assets (ROA) and Return On Equity (ROE). The research sample was selected using purposive sampling. The statistical test tool is SPSS 26 which is carried out using the classic assumption test and multiple linear regression analysis. The research results show that Capital Adequacy Ratio (CAR), Interest Expense to Total Loan (IETTL), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR) have a positive effect on Return on Assets (ROA). Non-Performing Loans (NPL), Operational Costs to Operating Income (BOPO), Net Open Position (PDN) have a significant and negative effect on Return on Assets (ROA). Meanwhile, Interest Expense on Total Loans (IETTL), Net Interest Margin (NIM) have a positive effect on Return on Assets (ROA). Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), Operational Costs to Operating Income (BOPO), Loan to Deposit Ratio (LDR) and Net Open Position (PDN) have a negative effect on Return on Assets (ROE).